Identification of a new p53/MDM2 inhibitor motif inspired by studies of chlorofusin. Issue 21 (1st November 2015) - Cominetti, Marco M.D.; Goffin, Sarah A.; Raffel, Ewan; Turner, Kerrie D.; Ramoutar, Jordann C.; O'Connell, Maria A.; Howell, Lesley A.; Searcey, Mark
Graphical abstract: Abstract: Previous studies on the natural product chlorofusin have shown that the full peptide and azaphilone structure are required for inhibition of the interaction between MDM2 and p53. In the current work, we utilized the cyclic peptide as a template and introduced an azidonorvaline amino acid in place of the ornithine/azaphilone of the natural product and carried out click chemistry with the resulting peptide. From this small library the first ever non-azaphilone containing chlorofusin analog with MDM2/p53 activity was identified. Further studies then suggested that the simple structure of the Fmoc-norvaline amino acid that had undergone a click reaction was also able to inhibit MDM2/p53 interaction. This is an example where studies of a natural product have led to the serendipitous identification of a new small molecule inhibitor of a protein–protein interaction.